Versatile nature of anthanthrone based polymers as active multifunctional semiconductors for various organic electronic devices. Issue 9 (19th November 2020) - Liu, Qian; Wang, Yang; Arunagiri, Lingeswaran; Khatib, Muhammad; Manzhos, Sergei; Feron, Krishna; Bottle, Steven E.; Haick, Hossam; Yan, He; Michinobu, Tsuyoshi; Sonar, Prashant
Abstract : The multi-purpose applications of low-cost anthanthrone dye based polymers in three different organic electronic devices are exploited. Abstract : The versatility of anthanthrone-based materials in organic electronics is exploited by synthesizing four polymers, PANT, PANT-TBO, PANT-TBT, and PANT-TffBT. PANT represents the self-coupled homopolymer, while the other three are D–A (donor–acceptor) type copolymers. Each of them is successfully applied in three different devices, namely organic field-effect transistors (OFETs), organic photovoltaic cells (OPVs), and chemical sensors. The results indicate that anthanthrone could be a very promising building block for the construction of semiconductors for multi-purpose applications. Specifically, the four polymers exhibit p-type properties in OFETs with hole mobility values in the range of 10 −4 –10 −3 cm 2 V −1 s −1 . In OPVs, the power conversion efficiencies (PCEs) of non-fullerene cells have a wide range from 0.28% to 5.21%. This indicates that the efficiency may reach a higher value via further structural modification by selecting suitable comonomers to produce new polymers. Additionally, based on the parameters of the OFET sensor devices and the variation in the backbone structures of the four polymers, they show varying response trends for four chemicals: octane, toluene, isopropanol and acetic acid, indicating the important role of the structural composition in generating different chemical sensitivities and fingerprints for sensing. Overall, we clearly disclose the potential of four new anthanthrone-based polymers in various types of electronic devices.